2017
DOI: 10.1042/bcj20160679
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-mediated oxidative stress: a common mechanism in tight junction disruption by different types of cellular stress

Abstract: The role of reactive oxygen species (ROS) in osmotic stress, dextran sulfate sodium (DSS) and cyclic stretch-induced tight junction disruption was investigated in Caco-2 cell monolayers in vitro, and restraint stress-induced barrier dysfunction in mouse colon in vivo. Live cell imaging showed that osmotic stress, cyclic stretch and DSS triggered rapid production of ROS in Caco-2 cell monolayers, which was blocked by depletion of intracellular Ca2+ by BAPTA. Knockdown of CaV1.3 or TRPV6 channels blocked osmotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 40 publications
1
42
0
2
Order By: Relevance
“…40,41 In the present study, our data showed that ETEC K88 challenge significantly increased the gene abundance and concentrations of IL-1β, IL-6, IL-8, and TNF-α in jejunum of piglets and IPEC-J2 cells. 45,46 Our data clearly showed that ETEC K88 challenge expression of p38 in IPEC-J2 cells. Oxidative stress is a very important mechanism in many potential mechanisms by which toxic substances affect mammalian cells.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…40,41 In the present study, our data showed that ETEC K88 challenge significantly increased the gene abundance and concentrations of IL-1β, IL-6, IL-8, and TNF-α in jejunum of piglets and IPEC-J2 cells. 45,46 Our data clearly showed that ETEC K88 challenge expression of p38 in IPEC-J2 cells. Oxidative stress is a very important mechanism in many potential mechanisms by which toxic substances affect mammalian cells.…”
Section: Discussionmentioning
confidence: 54%
“…44 Besides, evidences suggested that oxidative stress is closely related to intestinal barrier dysfunction, mainly due to the ability of oxidative stress to disrupt TJ proteins. 45,46 Our data clearly showed that ETEC K88 challenge expression of p38 in IPEC-J2 cells. Data are represented as means ± SEM, n = 6, *P < .05 vs CON group; # P < .05 vs ETEC K88 group.…”
Section: Discussionmentioning
confidence: 54%
“…18,39,40 Under oxidative stress conditions, reactive oxygen species synthesis can trigger greater prevalence of pathogenic microorganisms as a result of compromised immune cell functions, which could subsequently lead to defects in gastrointestinal barrier function. 41,42 The present study showed that there were no differences in activity of antioxidant enzyme and protein expression of occludin, claudin1 and claudin3 among pigs consuming colistin sulfate or lysozyme diets. These observations indicate lysozyme did not affect the antioxidant capacity and tight junction of growing pigs compared with colistin sulfate.…”
Section: Wileyonlinelibrarycom/jsfamentioning
confidence: 45%
“…In addition to morphology measurements, jejunal antioxidant capacity and tight junction were also analysed to explore intestinal health of growing pigs . Under oxidative stress conditions, reactive oxygen species synthesis can trigger greater prevalence of pathogenic microorganisms as a result of compromised immune cell functions, which could subsequently lead to defects in gastrointestinal barrier function . The present study showed that there were no differences in activity of antioxidant enzyme and protein expression of occludin, claudin1 and claudin3 among pigs consuming colistin sulfate or lysozyme diets.…”
Section: Discussionmentioning
confidence: 64%
“…In addition, claudin-18-null mice develop AEC hyperplasia and macrophage accumulation over time (89)(90)(91). Although a causal relationship between β 1 integrin and claudins has not been described, previous in vitro studies demonstrated that ROS can disrupt tight junctions (92)(93)(94), suggesting that β 1 integrin-mediated ROS could regulate tight junctions via effects on claudin expression. Another phenotype identified in β1 rtTA mice is AEC proliferation.…”
Section: Discussionmentioning
confidence: 99%